Countercultural: Subversive Resistance and the Neighborhood Congregation - Rendle, Gil (Rowman & Littlefield Publishers, 2023)
After decades of anti-institutionalism, here is a book that is honest about the importance of congregations and our need for them in our lives. Despite our lack of trust in institutions, we cannot live without them and still hope to live together in communities, let alone a nation. For important reasons our neighborhood institutions of religion (congregations) hold hope not found in other places. Politics and the economy have proven themselves gridlocked and incapable of breaking the narratives of fear and scarcity that now divide us. However, to step up into public space in order to offer what they hold as so important to these divided times, leaders of congregations need to understand why they are so countercultural and why being countercultural is an important role to play. This is not a time for congregations to try to fit into the culture and to worry about growing their membership and increasing their finances. It is not a time to let organizational anxieties determine next steps. What is required is courage – leaders courageous enough to speak openly with confidence of what they know, congregations courageous enough to seek new forms with which to offer the ancient wisdom that people still search for. As much as religious institutions are now needed, old forms no longer work in a fast and deeply changing culture. Instead of trying to improve what is already known, this book will provide a way for congregations to thrive and fulfill their purpose by being countercultural.